An Insight into the Therapeutic Potential of Phytobioactives for Diabetic Neuropathy - Eqbal, Asif; Kushwaha, Poonam; Kumar, Sanjay; Nisha, Ashmun; Ahsan, Rabiya; Asif, Md (Experimental and Clinical Endocrinology & Diabetes, 2025)
Diabetic neuropathy, a debilitating complication of diabetes, arises from chronic hyperglycemia-induced inflammation and oxidative stress, leading to progressive nerve damage. Current therapeutic strategies often focus on symptomatic relief rather than addressing the underlying pathophysiology. Emerging evidence highlights the therapeutic potential of phytobioactives with robust anti-inflammatory and antioxidant properties as promising alternatives for diabetic neuropathy management. Phytobioactives such as flavonoids, polyphenols, alkaloids, and terpenoids demonstrate significant potential by mitigating oxidative stress, inhibiting pro-inflammatory cytokines, and promoting neuroprotection. Furthermore, combination approaches utilizing the synergistic effects of these phytobioactives have shown enhanced efficacy in preclinical models, targeting multiple pathways involved in the progression of diabetic neuropathy. However, clinical translation is hindered by challenges including low bioavailability, chemical instability, and suboptimal dosage. This review explores the mechanistic roles, preclinical evidence, and clinical challenges of phytobioactives in diabetic neuropathy therapy, emphasizing the need for advanced formulation strategies and well-designed clinical trials to optimize their therapeutic potential. Leveraging these phytobioactives could pave the way for more effective and holistic diabetic neuropathy treatments.
Keywords: Diabetic neuropathy; phytobioactives; antioxidants; inflammation; oxidative stress; neuroprotection